Insight Into the Virulence Related Secretion Systems, Fimbriae, and Toxins in O2:K1 Escherichia coli Isolated From Bovine Mastitis - Sun, Min; Gao, Xing; Zhao, Kejie; Ma, Jiale; Yao, Huochun; Pan, Zihao (Frontiers in Veterinary Science, 2021)
Mastitis remains a major infection of the dairy cows and an important issue for the dairy farmers, and Escherichia coli (E. coli) bovine mastitis is a disease of significant economic importance in the dairy industry. Our study identified 6 isolates belong to the phylogroup B2 from 69 bovine mastitis E. coli strains. Except for one serotype O1 strain, all group B2 isolates were identified into the serotype O2, and showed significantly higher mortality in the mouse infection than other phylogroups’ strains. Genomic analyses and further tests were performed to examine the role of secretion systems, fimbriae and toxins during the systemic infection of O2:K1 strain BCE049. Two integral T6SS loci and three predicted effectors clusters were found to assemble the functional T6SS complex, and deliver diverse toxic effectors to modulate bacterial virulence in the mouse infection model. A total of four T4SS loci were harbored in the BCE049 genome, three of them are encoded in different plasmids, respectively, while the last one locates within the bacterial chromosome at FQU84_16715 to FQU84_16760, and was significantly involved in the bacterial pathogenicity. Numerous predicted pilus biosynthesis gene loci were found in the BCE049 genome, while most of them lost long fragments encoding key genes for the pili assembly. Unexpectedly, a type IV pilus gene locus locating at FQU84_01405 to FQU84_01335 in the plasmid 2, was found to be required for the full virulence of mastitis strain BCE049. It should be noted that a genetic neighborhood inserted with diverse genes is encoded by the plasmid 1, which harbors three prominent toxins including β-hemolysin, CNF2 and cytolethal distending toxin type III. Consequent studies verified that these toxins significantly contributed to the bacterial pathogenicity. These findings provide a molecular blueprint for understanding the underlying mechanisms employed by the bovine mastitis E. coli to colonize in host and cause systemic infection.